Potential Biomarkers for Diagnosis and Screening of Autism Spectrum Disorders - Anna Meiliana; Andi Wijaya (The Indonesian Biomedical Journal, 2014)
BACKGROUND: Autism spectrum disorder (ASD) is a highly heritable neurodevelopmental condition, which is typically characterized by a triad of symptoms: impaired social communication, social reciprocity and repetitive stereotypic behavior. While the behavioral phenotype of ASD is well described, the search for reliable ‘autism biomarkers’ continues.CONTENT: Insulin growth factor (IGF) is essential for the myelination of developing fetal neurons; this is in addition to the well-known links between IGF, maternal inflammation, infection and autism supporting IGF as a potential marker. Combining IGF data with data regarding levels of the known markers, serotonin and anti-myelin basic protein, in order to calculate an autism index, could provide a new diagnostic method for at-risk neonates. Disruptions to multiple pathophysiological systems, including redox, folate, methylation, tryptophan metabolism, and mitochondrial metabolism, have been well documented in autistic patients. Maternal infection and inflammation have known links with autism. Autoimmunity has therefore been a well-studied area of autism research. The potential of using autoantibodies as novel biomarkers for autism, in addition to providing insights into the neurodevelopmental processes that lead to autism.SUMMARY: The six proposed causes of autism involve both metabolic and immunologic dysfunctions and include: increased oxidative stress; decreased methionine metabolism and trans-sulfuration: aberrant free and bound metal burden; gastrointestinal (GI) disturbances; immune/inflammation dysregulation; and autoimmune targeting. A newborn screening program for early-onset ASD should be capable of utilizing a combination of ASD-associated biomarkers representative of the six proposed causes of autism in order to identify newborns at risk. The biomarkers discussed in this article are useful to guide the selection, efficacy and sufficiency of biomedical interventions, which would likely include nutritional supplementation, dietary changes and specific medications for treating GI pathogens and reducing inflammation.KEYWORDS: ASD, autism, biomarkers, newborn screening, diagnosis